An Ethnobotanical Survey of Indigenous Knowledge on Medicinal Plants Used by Communities to Treat Various Diseases around Ensaro District, North Shewa Zone of Amhara Regional State, Ethiopia - Mikias Teshome; Firew Kebede; Tamene Yohannes (Scientifica)
The study was conducted to investigate and document medicinal plants and associated knowledge on the utilization, management, preparation, and way of administration of the medicinal plant resources in Ensaro district, north Shewa zone, Ethiopia. A total of 100 informants were sampled from four study sites, and questionnaire surveys, semistructured interviews, ranking, and transect walk techniques were employed for data collection in midland, lowland, and highland agroecology and natural forests, riverine forests, and farmlands. Vast sources of the traditional healing knowledge of plant species conveyed from one generation to the next by word of mouth were from a family. A total of 101 medicinal plant species were identified from the study site, which belong to 95 genera and 49 families. These medicinal plants are used to treat about 35 types of human ailments. Families Fabaceae and Poaceae were represented by the highest number of medicinal plant species, followed by the Asteraceae, Lamiaceae, and Euphorbiaceae species. Out of the total medicinal plants’ species, 46.53% were herbs and 33.66% were shrubs. Most of them have medicinal properties in their leaf, root, seed, bark, stem, latex, sap seed, and fruits. Medicine from these plant parts is prepared in fresh, dried, and both fresh and dried states. The highest informant consensus was documented for the plant Ocimum lamiifolium used by 75% of informants for its medicinal value in treating fibril illness. Cucumis ficifolius and Eucalyptus globules are used by 41% and 39% of informants ranking second and third, respectively, for their medicinal value. This study revealed that indigenous knowledge of traditional medicine is still popular among local communities in the study area. The conservation strategy practiced by local people is not enough to tackle the erosion of plant species from their habitats. Thus, the conservation of these plants and the associated knowledge base is very essential.